Twittener - Lu, Mucheng (2016)
Twitter is one of the world’s most popular social media site. One of the main reasons why the micro-blogging platform quickly rose in popularity was because it provide users of the site a fast and concise way to get information, as well as follow the latest trends and topics online. This project aims to further improve that user experience by proposing an alternative way to interact with Twitter. Users will be able to listen to interesting tweets from Twitter, instead of the conventional way of reading them. This will allow users to get up to date with their Twitter news feed without the need to pay full attention to their computer screens or mobile devices. Additionally, this could also be potentially used by people with physical disabilities such as the visually impaired. For this project, two applications have been developed, a web application that allow users of the site to listen to tweets from Twitter, and a console application that will periodically crawl Twitter for interesting tweets and converting them from text to speech.